FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR - Indarti, Tia Sri; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Information related with the condition and financial performance or even the management performance is required by investors or business practitioners and the government in order to make economic decision. Consideration from various factors generally uses analysis as one of the ways to test whether the information which has been provided have benefits and can give prediction of the condition of the company in the future. The samples are 72 manufacturing companies which are listed in Indonesia Stock Exchange and these companies have been selected by using purposive sampling. The audit financial statement data has been obtained from the Indo-Exchange file. The hypothesis test has been done by using logistic regressions analysis in order to test the influence of operation leverage, profitability, firm size, firm age to the income smoothing are used as the hypothesis test. The classic assumption tests of the research model is the normality test to shows that the model in the research shows an abnormal result which means that the model can be analyzed by using the logistic regressions. Meanwhile, the multicolinearity test, the heteroscedasticity test, and the autocorrelation test do not have any problem. The result of this research shows that financial leverage does not have any positive influence to the income smoothing, profitability does not have any negative influence to the income smoothing, the firm size does not have any positive influence to the income smoothing and the firm company does have any negative influence to the income smoothing.Keywords: Income Smoothing, Operation Leverage, Profitability, Firm Size, Firm age